Length–weight and length–length relationships of five fish species collected from seagrass beds of the Sungai Pulai estuary, Peninsular Malaysia - Arshad, Aziz; Jimmy, A.; Nurul Amin, Sarker Mohammad; Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah (Blackwell Verlag, 2008)
Length–weight relationships are presented for five fish species from the seagrass beds of Peninsular Malaysia.